Re-Visiting of Plentiful Food Sources and Food Search Strategies in Desert Ants - Wolf, Harald; Wittlinger, Matthias; Bolek, Siegfried (Frontiers in Neuroscience, 2012)
North African desert ants, Cataglyphis fortis, are established model organisms in animal navigation research. Cataglyphis re-visit plentiful feeding sites, but their decision to return to a feeder and the organisation of food searches has been little studied. Here we provide a review of recent advances regarding this topic. At least two parameters determine the ants’ assessment of site quality, namely, amount of food available and reliability of food encounter on subsequent visits. The amount of food appears to be judged by the concentration of items at the food uptake site. Initially the amount of food in a feeder dominates the foragers’ decision to return, whereas learning about reliability takes precedence in the course of a few visits. The location of a worthwhile site is determined by the animals’ path integration system. In particular, the distance of the feeding site is memorised as the arithmetic average of the distances covered during the previous outbound and homebound journeys. Feeding sites that are small and inconspicuous cannot be approached directly with sufficient certainty, due to inevitable inaccuracies of the path integrator. Instead, desert ants steer downwind of the goal to encounter the odour plume emanating from the food and they follow this plume to the feeder. The angle steered downwind reflects the animals’ maximal navigation error and is adjusted according to experience. In summary, food searches of desert ants provide an unexpected wealth of features that may advance our understanding of search, navigation and decision strategies. There are several aspects that warrant further scrutiny.